Are parents' motivations to exercise and intention to engage in regular family-based activity associated with both adult and child physical activity?. Issue 1 (12th February 2017) - Solomon-Moore, Emma; Sebire, Simon J; Thompson, Janice L; Zahra, Jesmond; Lawlor, Debbie A; Jago, Russ
Abstract : Background/aim: To examine the associations between parents' motivation to exercise and intention to engage in family-based activity with their own and their child's physical activity. Methods: Cross-sectional data from 1067 parent–child pairs (76.1% mother–child); children were aged 5–6 years. Parents reported their exercise motivation (ie, intrinsic motivation, identified regulation, introjected regulation, external regulation and amotivation) as described in self-determination theory and their intention to engage in family-based activity. Parents' and children's mean minutes of moderate-to-vigorous-intensity physical activity (MVPA) and mean counts per minute were derived from ActiGraph accelerometers worn for 3 to 5 days (including a mixture of weekdays and weekend days). Multivariable linear regression models, adjusted for parent sex, number of children, indices of multiple deprivation and clustering of children in schools were used to examine associations (total of 24 associations tested). Results: In fully adjusted models, each unit increase in identified regulation was associated with a 6.08 (95% CI 3.27 to 8.89, p<0.001) min-per-day increase in parents' MVPA. Parents' external regulation was associated with children performing 2.93 (95% CI −5.83 to −0.03, p=0.05) fewer minutes of MVPA per day and a 29.3 (95% CI −53.8 to −4.7, p=0.02) accelerometer count-per-minute reduction. There was no evidence of association for the other 21 associations tested. Conclusions: Future family-based physical activity interventions may benefit from helping parents identify personal value in exercise while avoiding the use of external control or coercion to motivate behaviour.